Validation of the Scandinavian stroke scale in a multicultural population in Brazil - Luvizutto, Gustavo José [UNESP]; Monteiro, Tamiris Aparecida [UNESP]; Braga, Gabriel [UNESP]; Pontes-Neto, Octavio Marques; Lima Resende, Luiz Antônio de [UNESP]; Bazan, Rodrigo [UNESP] (Karger Publishers, 2012)
Background: The objective of this study was to evaluate the consistency, coherence, and interobserver reliability of the Portuguese version of the Scandinavian Stroke Scale (SSS) in a multicultural population of stroke. Methods: The SSS was translated, culturally adapted, and applied by two independent investigators. This was a randomized transverse study involving two groups: group 1 included 20 patients in the acute phase and group 2 included 20 patients in the subacute phase after stroke was confirmed by computed tomography with a pre-stroke modified Rankin Scale score of 0. Each patient also underwent National Institutes of Health Stroke Scale (NIHSS) evaluation at hospital entry and at the time of the SSS evaluation for correlation with our current standard hospital practice. Consistency and coherence were analyzed by Cronbach’s α and interobserver reliability by ĸ. Results: Forty patients were evaluated with 0.88 consistency and coherence in both stroke phases. Mean interobserver ĸ was 0.76, with reliability considered excellent and good for most scale items, and moderate for only the facial palsy item. Conclusion: The SSS is adequate and validated to study post-stroke patients in a multicultural Brazilian population and in the Portuguese language.
Keywords: Stroke stroke unit; Scandinavian Stroke scale; Stroke trials Brazil